Interaction of Portland cement hydration products with complex chemical additives containing fiberglass in moisture-proof cement compositions - Demina, O.I.; Plugin, A.A.; Dedenyova, E.B.; Bondarenko, D.O.; Kostuk, T.A.; Bondarenko, A.I. (Functional Materials, 2017)
Physicochemical studies of interaction of the hydration products of Portland cement with the complex chemical additives, which ensure the penetrating action of moisture-proof cement compositions with the borosilicate fiberglass, have been executed. It is established that the fiberglass tightly outgrows by such products of hydration as crystal hydrates and hydrosilicate gel, and durable electro-heterogeneous contacts are formed between them. It is established that one can not expect the destruction of the fiberglass in the alkaline medium of concrete block in view of the dense structure of the hydration products of. With the development of the moisture-proof cement compositions containing fiberglass it is recommended to give the preference to calcium salts, minimizing the content of sodium salts.